Pelatihan Penelitian Tindakan Kelas dan Penulisan Artikel Ilmiah bagi Guru SMP - Alexander, Ferdinant; Tari, Ezra; Liufeto, Martin Ch.; Messakh, Merling Tonia Litron Litos Conthes; Dami, Zummy Anselmus (Ilin Institute, 2023)
The goal of Community Service activities with the theme Writing and Publication of Classroom Action Research (CAR) is to increase educators' competence in the field of CAR, inspire innovation and improve learning, disseminate CAR knowledge and practice in the classroom, and encourage collaboration and knowledge sharing. The activity's goal was to reach 35 junior high school teachers in Kupang Regency, NTT Province. Carried out through the use of andragogy learning methodologies, including needs assessment, content preparation, and interactive training. The end findings demonstrate that the training participants' understanding of CAR has greatly expanded, their desire and self-innovation have developed, and they have continued with a commitment to use the outcomes of the CAR training, as well as subsequent training activities will be carried out in order to improve instructors' capacities to enhance their understanding and skills in CAR-related issues.